Measuring and managing patient expectations for breast reconstruction: impact on quality of life and patient satisfaction - Pusic, Andrea L (2012)
The goal of postmastectomy breast reconstruction is to restore a woman’s body image and to satisfy her personal expectations regarding the results of surgery. Studies in other surgical areas have shown that unrecognized or unfulfilled expectations may predict dissatisfaction more strongly than even the technical success of the surgery. Patient expectations play an especially critical role in elective procedures, such as cancer reconstruction, where the patient’s primary motivation is improved health-related quality of life. In breast reconstruction, assessment of patient expectations is therefore vital to optimal patient care. This report summarizes the existing literature on patient expectations regarding breast reconstruction, and provides a viewpoint on how this field can evolve. Specifically, we consider how systematic measurement and management of patient expectations may improve patient education, shared medical decision-making and patient perception of outcomes.